Further Opportunities to Reduce the Energy Use and Greenhouse Gas Emissions of Buildings. (September 2019) - Hsu, David; Meng, Ting; Han, Albert; Suh, Daniel
Buildings and energy systems are shaped within many different kinds of departments and agencies throughout local governments. This article argues that further opportunities exist to reduce the energy use of buildings and their associated greenhouse gas (GHG) emissions through the existing powers and jurisdiction of local governments. We use the example of New York City, where buildings produced 73 percent of all GHG emissions in 2014. By analyzing a data set of almost four thousand large buildings, we identify new opportunities for planners and other professionals to reduce energy use and GHG emissions by focusing on different mechanisms and/or collaborations.